Perilaku Membully pada Remaja: Kajian Literatur Faktor Penyebab dan Dampaknya - Chelsea Rizky Valentia; Aisyah Nurbaiti; Risma Anita Putriani (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Bullying among adolescents is an aggressive behavior carried out intentionally, repeatedly, and involving an imbalance of power between the perpetrator and the victim. This phenomenon is an important issue because it can affect adolescents’ psychological well-being, social relationships, and academic achievement in both the short and long term. This study uses a literature review method by collecting and analyzing recent national and international studies regarding the causes, forms, and impacts of bullying. The findings indicate that bullying is influenced by internal factors, such as low empathy, poor self-control, negative self-concept, and the desire for social recognition. In addition, external factors also contribute, including parenting styles, peer influence, unfavorable school climate, and the development of social media that increases the risk of cyberbullying. The impacts of bullying are experienced not only by victims, who may suffer from low self-esteem, anxiety, depression, and social withdrawal, but also by perpetrators, who are at risk of developing persistent aggressive behavior and reduced empathy. Therefore, cooperation among families, schools, and communities is needed to prevent and address bullying effectively.